2017
DOI: 10.1093/mnras/stx2582
|View full text |Cite
|
Sign up to set email alerts
|

The TESS–HERMES survey data release 1: high-resolution spectroscopy of the TESS southern continuous viewing zone

Abstract: The Transiting Exoplanet Survey Satellite (TESS) will provide high precision time-series photometry for millions of stars with at least a half-hour cadence. Of particular interest are the circular regions of 12-degree radius centered around the ecliptic poles that will be observed continuously for a full year. Spectroscopic stellar parameters are desirable to characterize and select suitable targets for TESS, whether they are focused on exploring exoplanets, stellar astrophysics, or Galactic archaeology. Here,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
126
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 54 publications
1
126
1
1
Order By: Relevance
“…Because APASS was not complete in the Southern sky at the start of observations, we use a synthetic V JK magnitude calculated from 2MASS photometry: V JK = K + 2(J − K + 0.14) + 0.382e ((J−K−0.2)/0.5) . Using PARSEC iscochrones (Marigo et al 2017) it was shown in Sharma et al (2018) that this transformation is reasonably accurate across the parameter space where the majority of GALAH stars fall. The GALAH observations are done in following three fixed magnitude ranges of V J K .…”
Section: Target Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because APASS was not complete in the Southern sky at the start of observations, we use a synthetic V JK magnitude calculated from 2MASS photometry: V JK = K + 2(J − K + 0.14) + 0.382e ((J−K−0.2)/0.5) . Using PARSEC iscochrones (Marigo et al 2017) it was shown in Sharma et al (2018) that this transformation is reasonably accurate across the parameter space where the majority of GALAH stars fall. The GALAH observations are done in following three fixed magnitude ranges of V J K .…”
Section: Target Selectionmentioning
confidence: 99%
“…If available and not flagged, stellar parameters from a prior version of The Cannon (version 1.3) are chosen. This version was also used for previous data releases of GALAH (Martell et al 2017), TESS-HERMES (Sharma et al 2018), and K2-HERMES (Wittenmyer et al 2018). If these parameters are flagged or not available, the synthesis commences with the stellar parameter estimates from the reduction process.…”
Section: Analysis Step 1: the Training Set Analysis With Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The mass of the stellar component is 4 × 10 8 M in either case, split among 4 × 10 4 particles. (Sharma et al 2018) programs. To maintain the survey selection function, we have applied the quality cuts summarised in Table 1, which gives a total of 465870 stars cross-matched with Gaia DR2.…”
Section: Profilementioning
confidence: 99%
“…Ligi et al 2016). Masses are more difficult to measure, so stellar atmosphere models are often used -as an example, Sharma et al (2018) constrain model-dependent masses for more than 10,000 stars using high resolution spectroscopy, with a median precision of 7%. Following these examples, we draw the radius and mass of the host star from normal distributions with widths of 3% and 7%, respectively.…”
Section: Prior Assumptionsmentioning
confidence: 99%